Needle‐Through‐Needle Technique in Lumbar Interlaminar Epidural Steroid Injection: A Case Report. Issue 7 (7th May 2020) - Zhang, Xiaolu Linda; Herzig, Samuel; Gritsenko, Karina; Hascalovici, Jacob; Dua, Simran; Shaparin, Naum
Abstract: When performing lumbar epidural steroid injection on obese patients, needle placement can be challenging due to the difficulty in estimating the appropriate needle length to utilize. Often times, the standard 3.5‐inch Tuohy needle is too short to reach its target. In our case report, a needle‐through‐needle technique was attempted in a lumbar interlaminar epidural steroid injection procedure after the initial needle fell short of the epidural space. To avoid removing the initial needle and restarting the procedure using a longer needle, a 20‐gauge 6‐inch Tuohy needle was inserted into the 17‐gauge 3.5‐inch Tuohy needle, successfully reaching the epidural space. This technique can facilitate quicker needle placement by avoiding the need for restarting the procedure with a longer needle. Thus, procedural time and radiation exposure may be decreased, as may patient discomfort from repeat needle insertions.